Answer :

Given that the quadratic equation (a – 12)x2 + 2(a – 12)x + 2 = 0 has equal roots

Comparing with standard quadratic equation Ax2 + Bx + C = 0


A = (a – 12) B = 2(a – 12) C = 2


Thus D = 0


Discriminant D = B2 – 4AC≥0


[2(a – 12)]2 – 4(a – 12)2≥0


4(a2 + 144 – 24a) – 8a + 96 = 0 using (a – b)2 = a2 – 2ab + b2


4a2 + 576 – 96a – 8a + 96 = 0


4a2 – 104a + 672 = 0


a2 – 26a + 168 = 0


a2 – 14a – 12a + 168 = 0


a(a – 14) – 12(a – 14) = 0


(a – 14)(a – 12) = 0


a = 14 or a = 12


for a = 12 the equation will become non quadratic – – (a – 12)x2 + 2(a – 12)x + 2 = 0


A, B will become zero


Thus value of a = 14 for which the equation has equal roots.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses